How are we really teaching our students? A paradox in pedagogy - Phillips, H.N.; Condy, J. (South African Journal of Higher Education, 2020)
This interpretive study is situated within a qualitative paradigm. The sample included four education faculties in South Africa. Data collection instruments comprised of focus-group and semi-structured interviews. Data was collected from final-year BEd students and their lecturers. An interpretation drawn from the results of this article is that most lecturers still subscribe to outmoded, authoritarian ways of teaching. Affiliation to this retrograde pedagogy limits the development of a dialogic relation between the lecturer and the student; feeding the notion of passive learning. Teacher educators should possess a knowledge of various teaching and learning theories; a large repertoire of teaching strategies. It is recommended that monitoring tools be introduced to ensure that all teacher educators have, or are in the process of, using a broader selection of methodologies to empower, inspire and sustain development of teachers.